Health and Migration: Health Securitization and Policy-Making Perspectives in the Post-Pandemic Era - Kyrgos, Zisis S.; Pantazis, Dimitrios G. (HAPSc Policy Briefs Series, 2021)
It is not to deny that the up-to-date literature has already discussed the emergence of forced human mobility due to the outbreak of health crises, owing to the latter’s adverse socio-political effects on the intrastate or regional systems. However, the ongoing COVID-19 pandemic has been playing a crucial role in enhancing the research upon health crises and health securitization, hence, further recognizing their multidimensional character. Under these circumstances, this text attempts to estimate whether and to what extent the states will reconsider their agendas –in the post-pandemic era– in terms of more successfully managing health crises and associated migration, so as to respectively reduce the potential negative consequences in their internal systems.